1928
DOI: 10.1111/j.1469-1809.1928.tb02066.x
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Brachydactylism and Interphalangeal Ankylosis

Abstract: The articles published by the Annals of Eugenics (1925–1954) have been made available online as an historical archive intended for scholarly use. The work of eugenicists was often pervaded by prejudice against racial, ethnic and disabled groups. The online publication of this material for scholarly research purposes is not an endorsement of those views nor a promotion of eugenics in any way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1951
1951
1979
1979

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The distal finger creases may be missing in digits 2, 3, and 5. Examination of 85 x-rays (Joachimstahl, 1898(Joachimstahl, , 1906Vidal, 1910;Scharff, 1912;Drinkwater, 1916;Hollander, 1918;Mohr, 1921;Pol, 1921;Hall, 1928;Behr, 1931;Stecher, 1936;Lossen, 1937;Becker, 1939;McNutt, 1946;Johnston and Davis, 1953;Haws, 1963;Bucke, 1964;Christiaens et al, 1965;Robinson et al, 1968;Cloherty, 1969;Temtamy and McKusick, 1969;Gnamey et al, 1971;Coberand et al, 1974;Rimoin et al, 1974;Rebollar, 1975;Fitch et al, 1979) revealed the following pattern.…”
Section: Short Stature Short Metacarpals and Distal Phalanges Fitchmentioning
confidence: 99%
“…The distal finger creases may be missing in digits 2, 3, and 5. Examination of 85 x-rays (Joachimstahl, 1898(Joachimstahl, , 1906Vidal, 1910;Scharff, 1912;Drinkwater, 1916;Hollander, 1918;Mohr, 1921;Pol, 1921;Hall, 1928;Behr, 1931;Stecher, 1936;Lossen, 1937;Becker, 1939;McNutt, 1946;Johnston and Davis, 1953;Haws, 1963;Bucke, 1964;Christiaens et al, 1965;Robinson et al, 1968;Cloherty, 1969;Temtamy and McKusick, 1969;Gnamey et al, 1971;Coberand et al, 1974;Rimoin et al, 1974;Rebollar, 1975;Fitch et al, 1979) revealed the following pattern.…”
Section: Short Stature Short Metacarpals and Distal Phalanges Fitchmentioning
confidence: 99%